Ballet Gesture Recognition and Evaluation System (Posé Ballet): Dynamic Improvement from Laboratory to Art Gallery - Apirath Limmanee; Pitsini Mano (My University, 2023)
This paper elaborates the continual development of “Posé Ballet,” our ballet gesture recognition and evaluation system using MS Kinect camera. After the technical side of the system is explained, we describe our “design thinking” concepts. With these concepts, our new and improved third-version software as well as GUI are developed to serve the visitors at Bangkok Art and Culture Centre (BACC). We also mention previous versions of hardware, software, and GUI such that readers get a sense of how the system is continually developed and transformed in accordance with requirements from specific user groups. At the end, some results and feedback are collected. These give us insight on how to improve our system further toward the goal of being standardized or commercialized.
Keywords: Human Pose and Action Recognition; Human Motion and Animation; Video Analysis and Summarization